2007
DOI: 10.1089/end.2006.0229
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Tubeless Percutaneous Renal Surgery

Abstract: Tubeless percutaneous renal surgery with an externalized ureteral catheter is a safe procedure that is suitable for any patient who can be rendered stone free with a single procedure regardless of the initial stone burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The postoperative retrograde study revealed minor extravasation in 14 patients (12%) and significant extravasation in three (2.3%). 22 Our retrospective evaluation of a consecutive series of 101 PCNLs performed at our institution over a 4-year period illustrates that a 'nephrostomy-free' PCNL is a safe procedure that leads to a decreased length of hospital stay (2.8 days vs 5.1 days; P < 0.001) decreased pain for the patient and, therefore, a reduced need for morphine-based analgesia. Of the 'nephrostomy-free' group, 23% used no morphine-based analgesia at all, compared to only 2.5% of the standard PCNL group (P < 0.001).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The postoperative retrograde study revealed minor extravasation in 14 patients (12%) and significant extravasation in three (2.3%). 22 Our retrospective evaluation of a consecutive series of 101 PCNLs performed at our institution over a 4-year period illustrates that a 'nephrostomy-free' PCNL is a safe procedure that leads to a decreased length of hospital stay (2.8 days vs 5.1 days; P < 0.001) decreased pain for the patient and, therefore, a reduced need for morphine-based analgesia. Of the 'nephrostomy-free' group, 23% used no morphine-based analgesia at all, compared to only 2.5% of the standard PCNL group (P < 0.001).…”
Section: Discussionmentioning
confidence: 86%
“…The catheters were removed by postoperative day 1 in 91% of patients. 21 Abou-Elela et al 22 performed 128 'tubeless' PCNLs with an external ureteric catheter. They had to convert 18 to 'tubed' PCNLs at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, they observed the advantages of decreased postoperative pain and discomfort, the need for analgesia, and a decrease in hospital stay [6][7][8]10] and cost [16]. However, the drawback was the need for re-cystoscopy, which is more invasive and may need general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Bellman and associates challenged the requirement for the routine placement of a nephrostomy tube after PNL and were the first to use the term tubeless PNL [5]. Since then there have been increased reports of tubeless PNL utilization [6][7][8][9][10][11]. In this study we present our experience with tubeless PNL, with very limited exclusion criteria as part of the new era of percutaneous renal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported by Ashraf Abou-Elela et al . [37] in 128 patients and Gupta et al . [38] in a study of 69 patients [Table 1].…”
Section: Percutaneous Nephrolithotomy With An Externalized Ureteral Cmentioning
confidence: 99%